The Correlation Between Financial Profitability And Stock Market Performance Of Companies Listed On The Bucharest Stock Exchange - PREDA BUZGURESCU Olimpia Livia (Journal of Economic and Social Development (Varaždin), 2020)
This paper highlights the correlation between financial profitability and the performance of the stock market of the companies listed on the Bucharest Stock Exchange. The sample consists of 30 Romanian companies from different fields of activity to compare the profitability with the financial structure to highlight the change in the market value of the shares. For highlighting the profitability of the companies, we used the economic rate of return on assets, the rate of financial return and the rate of return on sales, and measuring the stock market performance the market capitalization and the price earning ratio. This subject is very important for all investors in the capital market, regardless of the area of activity of the companies, because the financial profitability and the performance of the stock market are relevant indicators for financial investments.